Altered Regulation of KIAA0566, and Katanin Signaling Expression in the Locus Coeruleus With Neurofibrillary Tangle Pathology - Andrés-Benito, Pol; Delgado-Morales, Raul; Ferrer, Isidro (Frontiers in Cellular Neuroscience, 2018)
The locus coeruleus (LC), which contains the largest group of noradrenergic neurons in the central nervous system innervating the telencephalon, is an early and constantly vulnerable region to neurofibrillary tangle (NFT) pathology in aging and Alzheimer’s disease (AD). The present study using whole genome bisulfite sequencing and Infinium Human Methylation 450 BeadChip was designed to learn about DNA methylation profiles in LC with age and NFT pathology. This method identified decreased DNA methylation of Katanin-Interacting Protein gene (KIAA0566) linked to age and presence of NFT pathology. KIAA0566 mRNA expression demonstrated with RT-qPCR significantly decreased in cases with NFT pathology. Importantly, KIAA0566 immunoreactivity was significantly decreased only in LC neurons with NFTs, but not in neurons without tau pathology when compared with neurons of middle-aged individuals. These changes were accompanied by a similar pattern of selective p80-katanin reduced protein expression in neurons with NFTs. In contrast, p60-katanin subunit expression levels in the neuropil were similar in MA cases and cases with NFT pathology. Since katanin is a major microtubule-severing protein and KIAA0566 binds and interacts with katanin, de-regulation of the katanin-signaling pathway may have implications in the regulation of microtubule homeostasis in LC neurons with NFTs, thereby potentially interfering with maintenance of the cytoskeleton and transport.